Dynamics of Monetary Policy Comparative Study Between Indonesia and Malaysia - Mugni Muhit; Yadi Janwari; Sofyan Al-Hakim (al-Afkar, Journal For Islamic Studies, 2024)
In countries that embrace a dual banking system, such as Indonesia and Malaysia, the monetary policy implemented is also a multiple monetary policy. Both Islamic and conventional monetary policies have the same goal, which is to create stable money value and full employment. This article aims to analyze the transmission of convergence monetary policy implemented by Indonesia and Malaysia with two objectives: first, to identify the transmission channel of dual monetary policy in Indonesia and Malaysia; second, to compare the effectiveness mechanism of dual monetary policy implementation in Indonesia and Malaysia. The analysis of several empirical studies concludes that the transmission channels, both Islamic and conventional in the monetary policy of dual banking system in Indonesia and Malaysia are the same, but the tendency of the channel depends on the real conditions of each country's economy. The mechanism of the effectiveness of monetary policy transmission in Indonesia and Malaysia is almost similar, namely the transmission instruments of Islamic monetary policy and or elements of Islamic banking that can withstand inflation as well as increase economic growth and development.